Foundations for a Scientific Analysis of Value - Kraft, V. author. aut Link
XVII, 198 p.
Keywords: In English-speaking countries Victor Kraft is known principally for his account of the Vienna Circle. ! That group of thinkers has exercised in recent decades a significant influence not only on the philosophy of the western world, but also, at least indirectly, on that of the East, where there is now taking place a slow but clearly irresistible erosion of dogmatic Marxism by ways of think ing derived from a modem scientific conception of the world. Kraft's work as historian of the Vienna Circle has led to his being classed, without further qua1ification, as a neo-positivist philosopher. It is, however, only partially correct to count him as such. To be sure, he belonged to the group named, he took part in its meetings, and he drew from it suggestions central to his own work; but he did not belong to the hard core of the Circle and was a con scious opponent of certain radical tendencies espoused, at least from time to time, by some of its members. Evidence of this is provided by the theory of value now presented in English translation, since no less a thinker than Rudolf Carnap had, originally at any rate, obeyed a very narrowly conceived criterion of sense and declared value judgements to be senseless.